L’assurance et le projet de construction - Hesler, Nicole Duval (Assurances, 1989)
The author discusses various insurance problems related to construction projects: prior to undertaking the work, while work is in progress and after it has been accepted. The problems examined include errors in tenders, the liability of the parties involved in the act of construction, prescription and questions relating to environmental damage.